MINAT ORANG TUA DALAM MENYEKOLAHKAN ANAK DI MTS THAMRIN YAHYA KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Wirdatul Jannah; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was conducted in the village of Rambah Hilir Tengah in the Rambah Hilir District, Rokan Hulu Regency. The purpose of this study aims to determine the interest of parents in sending their children to MTs Thamrin Yahya. The focus topic of this research is about children’s education. The sample in this study amounted to 75 people. Researchers use quantitative methods and use census technique. Data instruments are observation, questionnaires and documentation. This research provides an explanation that the interest of parents in sending their children to MTs Thamrin Yahya as education for MTs or SMP. Parental interests that underlie and drive one’s behavior in social action. Behavior based on social structures in the form of habist and traditions from the community, beliefs, driving factors that make the parents of Rambah Hilir Tengah village interested in sending thei children to MTs Thamrin Yahya. Encouragement of mobilization, namely the development of every science and technology, social control in providing supervision to children who attend school at MTs Thamrin Yahya in the fields of behavior, attitudes, Children’s character. Whit the interest of the parents the village of Rambah Hilir Tengah who send their children to MTs Thamrin Yahya based on the parents and the support of the children who want to go to school because that interest comes from someone’s desire to take action. Keywords: Interest, views, attitude, action